Evidence for hybridization between sympatric holm-oak and cork-oak in Spain based on diagnostic enzyme markers - Elena-Rossello, J. A.; Lumaret, R.; Cabrera, E.; Michaud, H. (Plant Ecology, 1992)
Hybridization has been detected in mixed populations of juvenile cork-oak and holm-oak individuals using three diagnostic enzyme loci coding for esterases, leucine amino peptidases and acid phosphatases respectively. Among the 35 studied individuals, 29, 5 and 1 were identified as holm-oak, cork-oak and hybrid respectively. Such diagnostic markers are likely to be useful to detect and remove hybrids at the juvenile stage in areas where the holm-oak is grown for acorn production and the cork-oak is cultivated for cork. This is necessary since hybrid adults produce neither cork nor acorns of high quality.
Keywords: cork-oak; enzyme markers; holm-oak; Hybridization; Quercus